PENGARUH KOMITMEN ORGANISASIONAL TERHADAP MOTIVASI KERJA, KEPUASAN KERJA DAN KINERJA KARYAWAN (Studi pada Karyawan CV. Perkasa Mandiri Sejati Grobogan) - Zaumi K. Zessy Styanadi, 10.05.51.0091; Astuti, Sih Dharmi (Students Journal of Economic and Management, 2014)
The purpose of this study was to analyze the effect of organizational commitment on work motivation, job satisfaction and employee performance. The samples were all employees of CV. Perkasa Mandiri amounting to 72 straight. Test equipment in this study using multiple linear regression. The results of this study indicate that high employee motivation due to the direct effect of organizational commitment. While employee satisfaction is higher when the direct influence of organizational commitment and work motivation. Neither the fastest performance will increase due to the direct influence of organizational commitment, high work motivation and job satisfaction are highKeywords: organizational commitment, work motivation, job satisfaction and employee performance